Low Cost Technology for Increasing Crop Productivity under Sustainable Agriculture - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
Global warming, drought, salinity, heat stress and other abiotic stress factors associated with ever increasing human populations are affecting greatly crop productivity and threatening food security globally. In this respect it may be mentioned two-thirds of world arable lands are affected by salinity and more than one-third is affected by drought, besides heat stress, flooding, deficiency of nutrients etc. Enormous research inputs have been directed to address these problems with reasonable success, but little success has been achieved to transfer the technology to the farmers for their immediate benefits.